Are Young and Small Firms Hothouses for Nascent Entrepreneurs? Evidence from German Micro Data - Joachim Wagner (Institute for the Study of Labor (IZA), 2004)
Using a large recent representative sample of the German population this paper contributes to the entrepreneurship literature by empirically testing the hypothesis that young and small firms are hothouses for nascent entrepreneurs. The empirical estimation takes the rare events nature of becoming a nascent entrepreneur and the regional stratification of the sample into account. Controlling for various individual characteristics and attitudes (sex, age, risk aversion, presence of a role model in the family, and the width of professional background) we illustrate both the statistical significance and the economic importance for entrepreneurship of work experience in a firm that is both young and small.
Keywords: R12; J23; 330; entrepreneurship; young and small firms; rare events logit; Germany; Unternehmer; Klein- und Mittelunternehmen; Unternehmensgründung; Schätzung; Deutschland